The Concept of Competence-Competence: An Indonesian Approach - Atika Dewi, Ayu; Jamil, Abdul (KnE Social Sciences, 2023)
In international arbitration, the concept of competence-competence, which allows an arbitral tribunal to make decisions in cases within its own jurisdiction, is regarded as a fundamental principle. However, state adoption of the notion into their national law has shown that each nation applies this principle in different ways. In order to understand how the principle of competence-competence is used in the jurisdiction of Indonesian courts, it is important first to understand the country’s legal system. Our findings demonstrated that the Indonesian legal system needs to clearly apply the competence-competence concept, making it challenging to use the legal basis for arbitration in deciding cases within its own jurisdiction. This affects the Indonesian courts’ recognition of the principle, which has yet to be applied in accordance with the original provision. The authors suggest that Indonesia acknowledge and incorporate the competence-competence concept into its national law so that the principle can guide the court’s practice. Adopting this principle into federal legislation can improve the efficiency of arbitration and contribute to Indonesia becoming a nation with a supportive arbitration environment. Keywords: Arbitration, Competence-Competence, Arbitral Competence